Streptococcus pneumoniae detection by polymerase chain reaction aiding diagnosis in hemolytic uremic syndrome - Paize, Fauzia; Pipon, Madeleine; Judd, Brian; Jones, Caroline A. (Journal of Pediatric Infectious Diseases, 2006)
Hemolytic uremic syndrome induced by Streptococcus pneumoniae is the second most common cause of hemolytic uremic syndrome. This case report details a child who was diagnosed with pneumococcal induced hemolytic uremic syndrome on a polymerase chain reaction sample only. No pathogens were isolated from any other medium. The isolation of S. pneumoniae made a significant impact on the clinical management of the child. This report emphasizes the importance of polymerase chain reaction as a molecular biological technique for the detection of streptococcal infection.
Keywords: Hemolytic uremic syndrome; Streptococcus pneumoniae